Long time existence of hyperbolic Ricci-Bourguignon flow on Riemannian Surfaces - Mehrad Mohammadi; Shahroud Azami (IndoMS, 2020)
We consider the hyperbolic Ricci-Bourguignon flow(HRBF) equation on Riemannian surfaces and we find a sufficient and necessary condition to this flow has global classical solution. Also, we show that the scalar curvature of the solution metric gij convergence to the flat curvature.